Clinical study of active squamosal chronic otitis media - Rajashekhar, Rashmi P.; Anand, Rohit; Mahajan, Gundappa D.; Gowtham, K.; Rathi, Parul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Cholesteatoma term was coined by Johannes Muller in 1838. Cholesteatomas are the last stage of squamous epithelial retraction comprising either the pars tensa or flaccida that are not self-cleansing, which retain epithelial debris and elicit a secondary, inflammatory reaction. Active squamosal epithelial disease is a retraction pocket which is filled with keratinous debris. Methods: 50 patients were selected presenting with active squamosal chronic otitis media (COM). For all cases a detailed history was taken, otoscopic and otomicroscopic examination along with tuning fork test were performed to know the status of tympanic membrane and status of air and bone conduction of sound waves. Audiological assessment was done by pure tone audiometry. X-ray mastoid and high-resolution computed tomography (HRCT) temporal bone was done for analysis. Pre anaesthetic fitness was taken and patients were posted for tympanomastoid exploration. Results: Most common presentation was of foul smelling otorrhoea in 40 patients, reduced hearing in 40 patients. 8 patients presented with vertigo and 2 presented with facial nerve paresis. Most common otoscopic finding was pf postero-superior retraction pocket in 26 patients. After clinical and radiological assessment 30 patients were posted for canal wall down mastoidectomy. Conclusions: Primary acquired cholesteatomacan affect all age group with significant effect on hearing and quality of life.